2018
DOI: 10.1111/are.13794
|View full text |Cite
|
Sign up to set email alerts
|

Growth, survival rate and fatty acid composition of sterlet (Acipenser ruthenus ) larvae fed fatty acid-enriched Artemia nauplii

Abstract: We evaluated the growth and survival rate of sterlet (Acipenser ruthenus) larvae fed Artemia nauplii enriched with Olioω3 or Red Pepper commercial emulsions (BernAqua NV, Belgium). Sterlet larvae, 0.022 ± 0.002 g body weight, were randomly assigned to one of three feeding regimes with two different feeding durations. After administering live feed for 7 or 14 days, larvae were weaned onto commercial food and reared to 36 days posthatching (28 days of feeding). There were no significant differences in body weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…comm. Twining et al (2019) Harpacticoid copepods (Heteropsyllus nunni) Lepidopterans Williams and Biesiot (2004) Vukašinović et al (2015); Hemmati et al (2017) et al (2018) Cartland-Shaw et al (1998) Waugh et al (2012) Body condition indexes -weight to length -fat mass Tree Swallows (Tachycineta bicolor) Humans (Homo sapiens) Round gobies and Monkey gobies Twining et al (2016) Tan (2014); Elias and Innis (2001) Ghomi et al (2014et al (2000); Ilić et al (2019) Twining et al (2016) Twining et al (2019) Glencross (2009); Zhou et al (2020)Lundova et al (2018)…”
mentioning
confidence: 99%
“…comm. Twining et al (2019) Harpacticoid copepods (Heteropsyllus nunni) Lepidopterans Williams and Biesiot (2004) Vukašinović et al (2015); Hemmati et al (2017) et al (2018) Cartland-Shaw et al (1998) Waugh et al (2012) Body condition indexes -weight to length -fat mass Tree Swallows (Tachycineta bicolor) Humans (Homo sapiens) Round gobies and Monkey gobies Twining et al (2016) Tan (2014); Elias and Innis (2001) Ghomi et al (2014et al (2000); Ilić et al (2019) Twining et al (2016) Twining et al (2019) Glencross (2009); Zhou et al (2020)Lundova et al (2018)…”
mentioning
confidence: 99%
“…Previous studies on Murray cod (Maccullochella peelii peelii) and seahorse (Hippocampus abdominalis) larvae found that Algamac 3050 performed best in terms of growth performance among several Artemia enrichment products (Woods 2003;Francis et al 2019), which is consistent with our study. However, meagre (Argyrosomus regius) and sterlet (Acipenser ruthenus) larvae showed higher growth performance when fed Red Pepper enriched Artemia (Campoverde and Estevez 2017;Lundova et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Neither the growth nor survival was impaired in the current research and therefore the use of the higher density to increase fish biomass gain seems justified. Several studies on different factors are available in sterlet larvae, in which stocking densities commonly used are between 2.5 and 17 sterlet larvae L −1 (Feledi & Rónyai, 2013; Laczynska et al, 2020; Lundova et al, 2018; Rybnikár et al, 2011). According to Chebanov and Galich (2011) norm for endogenous feeding phase stocking density is 7000 larvae per m 2 , while the data for already feeding larvae are not provided.…”
Section: Discussionmentioning
confidence: 99%
“…Freshly hatched larvae feed exclusively endogenously on the yolk sac contents for approximately 7 days under given culture conditions (Lundova et al, 2018). Since the 8 DPH natural feed in form of freshly hatched Artemia sp .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation